PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPS MENGGUNAKAN MEDIA ANIMASI - Dedy Miswar; yarmaidi yarmaidi; Yuniyarsih Yuniyarsih (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
Abstract: This research aimed to: improve the learning activities, and learning outcomes at class VII-1 of SMPN 1 Sungkai Selatan. This research used descriptive method with classroom action research which was conducted in three cycles. The subjects of this research were 36 students from class VII-1 which consist of 20 female students and 16 male students. The data that taken were the result of the end of the cycle and the observation of learning activities and learning outcomes. The result of this research showed that in first cycle, students learning activities reach 52,78% and where as the results of learning outcomes completeness reached 44,44%. In the second cycle students learning activities increased into 64,58%, and the learning outcomes completeness also increased to 52,78%. In the third cycle which one to be the result of this research showed, students learning activities increased to 75,69%, the percentage of learning outcomes completeness also increased to 80,55%. Based on those result, it can be concluded that teaching through media animation can improve the learning activities, and learning outcomes IPS.